The Prevalence and Related Effects of HIV Drug-Resistant Strains Against Antiretroviral Therapy in China. Issue 2 (17th June 2022) - Xing, Hui; Ruan, Yuhua; Liao, Lingjie; Shao, Yingming
Abstract : Abstract: Anti-human immunodeficiency virus (HIV) treatment resistance surveillance has been going on for nearly 18 years in China. In this paper, we review the prevalence in China of resistance to reverse transcriptase and protease inhibitors in the HIV-infected population receiving antiretroviral therapy (ART) and the population that stopped ART in recent years. Drug resistance is an important factor affecting the death of patients with acquired immune deficiency syndrome (AIDS). With the extension of the duration of ART and the expansion of the population receiving ART, especially the widespread promotion of preventive drugs before and after exposure, it is important to obtain insight into the prevalence and types of drug-resistant strains and their impact on the overall AIDS prevention and treatment effect.